1996
DOI: 10.1074/jbc.271.8.4477
|View full text |Cite
|
Sign up to set email alerts
|

A Transient Precursor of the HIV-1 Protease

Abstract: Recently, the mechanism of autoprocessing of the protease (PR) of the human immunodeficiency virus type 1 from the model polyprotein, MBP-DeltaTF-PR-DeltaPol, which contains the protease linked to short native flanking sequences (DeltaTF and DeltaPol) fused to the maltose binding protein (MBP) of Escherichia coli, was reported (Louis, J. M., Nashed, N. T., Parris, K. D., Kimmel, A. R., and Jerina, D. M. (1994) Proc. Natl. Acad. Sci. U. S. A. 91, 7970-7974). According to this mechanism, intramolecular cleavage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
50
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 20 publications
7
50
0
Order By: Relevance
“…The first step involves an intramolecular cleavage of the N terminus that is followed by intermolecular cleavage of the C terminus (19,21). A relatively low K m for peptide substrates representing the p6*-PR (where p6* is TFPϩp6 pol ) cleavage site, compared with that for oligopeptides corresponding to other Gag or Pol cleavage sites (23) supports the view that the Nterminal cleavage is an early event in the proteolytic cascade.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…The first step involves an intramolecular cleavage of the N terminus that is followed by intermolecular cleavage of the C terminus (19,21). A relatively low K m for peptide substrates representing the p6*-PR (where p6* is TFPϩp6 pol ) cleavage site, compared with that for oligopeptides corresponding to other Gag or Pol cleavage sites (23) supports the view that the Nterminal cleavage is an early event in the proteolytic cascade.…”
mentioning
confidence: 65%
“…Earlier studies have shown that premature activation or partial inhibition of the protease leads to retarded viral maturation (15)(16)(17)(18). Hence understanding the exact sequence of protease maturation from the Gag-Pol precursor has gained importance in recent years because of its intrinsic importance in viral maturation and as a target for drugs against AIDS (19).…”
mentioning
confidence: 99%
“…Structural analyses of mature protease dimers alone cannot fully explain the autoprocessing mechanism or reveal the cause of drug resistance. Proviral DNA mutagenesis on the other hand has provided insightful information regarding protease autoprocessing mechanism [14,19-22,24,28], however, sensitive and direct detection of the mature protease, along with its precursor and processing intermediates, has been restrained due to lack of highly specific and sensitive antibodies. Consequently, most information is indirectly derived from analysis of Gag processing efficiency and/or p24 production [14,24].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Between the two cleavage sites that lead to liberation of the mature protease, the C-terminal cleavage seems to have less of an impact on the regulation of autoprocessing as mutations blocking this cleavage have no significant influence on protease activity or Gag processing in transfected mammalian cells [19,20]. In contrast, mutations blocking N-terminal cleavage abolish Gag processing and lead to loss of viral infectivity [21,22], suggesting that N-terminal cleavage plays an important role in regulating autoprocessing.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the flanking C-terminal residues (reverse transcriptase region), which do not appear to affect the catalytic activity or the K d in fusion with the protease (9,22,23), the native transframe region, which flanks the N terminus of the protease in the Gag-Pol precursor, drastically influences the dimer stability of the protease indicated by the very low catalytic activity of the protease prior to its maturation at its N terminus ( Fig. 1) (10, 11).…”
mentioning
confidence: 99%